p-type Bi0.4Sb1.6Te3 nanocomposites with enhanced figure of merit - Fan, Shufen (2014)
We report enhanced figure of merit, ZT, in p-type Bi0.4Sb1.6Te3 nanocomposites fabricated by a rapid and high throughput method of mixing nanostructured Bi0.4Sb1.6Te3 particles obtained through melt spinning with micronsized particles obtained via solid state reaction. Due to effective scattering of phonons over a wide wavelength spectrum, low thermal conductivity, and moderately good power factor were obtained in the nanocomposites to achieve ZT above 1.5 at room temperature. A maximum ZT of 1.80 was attained at 43 °C for the nanocomposite consisting 40 wt % nanoinclusions. This was a 56% increment over the bulk sample, and the highest ZT reported for Bi2Te3-based materials.